Peoria's fund accounting software aids reporting. (American City & County, 1997)
Officials at the treasurer's office in Peoria County, Illinois, are using the Integrated Fund Accounting System software package from BI-Tech Software, Chico, California. By using the software, employees can now create virtually any accounting or financial report required. A major advantage of the software is the real-time posting capability, which saves time by eliminating the need for batch posting at the end of every night. Instead, real-time posting is carried out at the main office and outside buildings, including a nursing home seven miles away.